2012
DOI: 10.1016/j.ultsonch.2011.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultrasound treatment on steady and dynamic shear properties of glucomannan based salep dispersions: Optimization of amplitude level, sonication time and temperature using response surface methodology

Abstract: The present study investigated effect of different amplitude levels (40, 70 and 100%), sonication temperatures (40, 50 and 60°C) and exposure times (3, 7 and 11 min) on steady shear properties; apparent viscosity (η), shear stress (σ), consistency coefficient (K), flow behavior index (n) and dynamic shear properties; storage modulus (G'), loss modulus (G″), complex viscosity (η(∗)), complex modulus (G(∗)) and loss tangent (tan δ) values of glucomannan based salep solution (SS) and salep drink (SD) samples. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…As can be clearly observed, we developed a polysaccharide ultrasonic assisted extraction process that the ultrasonic treatment facilitates the release of polysaccharides from inside the cells to the exterior solvent. However, at high vibration amplitude, a great number of cavitation bubbles are generated in the solution, which may dampen sound energy passing through the liquid (Karaman et al ., ). The present study indicated that ultrasound waves give a larger yield only at 40 W.…”
Section: Resultsmentioning
confidence: 97%
“…As can be clearly observed, we developed a polysaccharide ultrasonic assisted extraction process that the ultrasonic treatment facilitates the release of polysaccharides from inside the cells to the exterior solvent. However, at high vibration amplitude, a great number of cavitation bubbles are generated in the solution, which may dampen sound energy passing through the liquid (Karaman et al ., ). The present study indicated that ultrasound waves give a larger yield only at 40 W.…”
Section: Resultsmentioning
confidence: 97%
“…Ultrasound treatment for long duration expedite depolymerization process extremely. These resulted in weakening of the interaction between the polymer molecules and decreasing viscosity by destruction of the gel network subsequently (Azizi & Farahnaky, ; Jambrak et al, ; Karaman et al, ). Also, hardness values are shown in Table indicated that the power of treatment has less effect on it, in comparison with the time of sonication.…”
Section: Resultsmentioning
confidence: 99%
“…All these techniques have confirmed the process divided into several stages. decreasing viscosity by destruction of the gel network subsequently (Azizi & Farahnaky, 2013;Jambrak et al, 2010;Karaman et al, 2012).…”
Section: Effect Of Ultrasound On the Gel Texturementioning
confidence: 99%
See 1 more Smart Citation
“…The interactions between the polymer molecules were weakened, and this destruction of the polymer network resulted in a decrease of viscosity. 28 …”
mentioning
confidence: 99%